Motif Penggunaan Channel YouTube Penerimaan Mahasiswa Baru (PMB) UHAMKA sebagai Media Informasi - Maududi, Mukhlish Muhammad; Rahman, Nurlina; Putra, Gilang Kumari; Ihsan, Ihsan; Febriana, Mulea; Ekowati, Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Information channels at this time are very diverse with the development of information and communication technology, as well as in the information dissemination process carried out by the University of Muhammadiyah Prof. Dr. Hamka (Uhamka) who uses YouTube as a medium to socialize new student registration information, which is also charged with entertainment to attract the number of visitors. This research was designed with the aim of determining the motives of the audience of the Uhamka New Student Admissions (PMB) vlog channel. This research uses a descriptive qualitative research method with data collection techniques in the form of literature and documentation of interview fibers for 6 (six) Uhamka students. Vlog channel PMB Uhamka is the research subject chosen by the researcher. This study uses McQuail's motive theory, namely: information motives, personal identity motives, social interaction motives, and entertainment motives. The results showed that the audience freely chooses what media to choose to get information, its users have control over what they want to know and what media is chosen. Media users have the ability to choose what to consume to satisfy needs through the media. From the results of the interviews, it is also known that information motives and entertainment motives are the dominant motives.